1997
DOI: 10.1021/jp972002k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Photocatalytic Reactions under Extremely Low-Intensity UV Illumination on Titanium Dioxide Thin Films

Abstract: The photocatalytic decomposition efficiency of gaseous 2-propanol was studied using a titanium dioxide thin film under very weak UV light; the incident UV light intensity was 36 nW−45 μW·cm-2. Under such low-intensity UV illumination, the value of the quantum yield (QY) increased gradually with decreasing number of absorbed photons and finally saturated (28%) for a number of absorbed photons less than 4 × 1011 quanta·cm-2·s-1 for an initial 2-propanol concentration of 1000 ppmv. Thus, purely light-limited cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
304
3
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 459 publications
(333 citation statements)
references
References 30 publications
(58 reference statements)
17
304
3
3
Order By: Relevance
“…For this study, the illumination intensity at the powder surface was set as 6600 Lux (LX-105; Custom Co., Tokyo, Japan). As described in an earlier report, 30),31) molecules of gaseous IPA are initially decomposed into acetone. They are then finally decomposed to H 2 O and CO 2 .…”
Section: Characterizationmentioning
confidence: 80%
See 1 more Smart Citation
“…For this study, the illumination intensity at the powder surface was set as 6600 Lux (LX-105; Custom Co., Tokyo, Japan). As described in an earlier report, 30),31) molecules of gaseous IPA are initially decomposed into acetone. They are then finally decomposed to H 2 O and CO 2 .…”
Section: Characterizationmentioning
confidence: 80%
“…30),31) Before evaluation, UV pre-illumination (0.7 mW/cm 2 at 365 nm) onto the sample TiO 2 powder was conducted using a black light bulb for one night (more than 8 h) to remove organic compounds that had been adsorbed onto the surface. Then sample TiO 2 powder (40 mg) was set at the center of a Pyrex glass vessel with a quartz lid (500 ml in volume) in the area of 10.2 cm 2 .…”
Section: Characterizationmentioning
confidence: 99%
“…Such differences are expected to affect the rate difference in IPA decomposition and CO 2 generation because the reported photocatalytic decomposition pathway of gaseous IPA includes several reaction steps. 24), 25) Detailed analysis of the relation between characteristics of Fe-modified TiO 2 and the decomposition performance of various organic compounds will be undertaken in future work.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that quantum yields in dilute aqueous suspensions are usually below ~10% while quantum yields of oxidation of organic species in the gas phase exceed 50% under weak UV illumination [7,12,29]. Various methods of improving efficiency have been studied, for example doping of catalysts to enhance efficiency by inhibiting charge carrier recombination or improving light absorption is well reported in the literature [30][31][32][33][34].…”
Section: Enhancement Of Photocatalytic Efficiencymentioning
confidence: 99%